PENGARUH EKSPOR IMPOR TERHADAP TRANSAKSI BERJALAN INDONESIA SEBELUM DAN SESUDAH SUBPRIME MORTGAGE - Mayong Noor Bagaskoro (Ecoplan, 2019)
This study is to determine the effect of exports and imports on the current account of Indonesia and comparison before and after the 2008’s subprime mortgage crisis. The analytical method used is mutiple regression and strcutural break test. The regression results show that exports have positive effect and imports have negative effect on current account of Indonesia. While the structural break test show that there are differences in the comparison effect of export and import on the current account of Indonesia in the before and after the crisis.